EFEKTIFITAS PIJAT ESSENTIAL OIL LEMONGRAS TERHADAP PENURUNAN DISMENORE PADA REMAJA PUTRI - Herlina Simanjuntak; Binka Ajeng Sakti Wulandari; Atin Rustini (JOMIS (Journal of Midwifery Science), 2025)
Dysmenorrhea is caused by uterine muscle spasms during painful menstruation. In Indonesia, the incidence of dysmenorrhea is quite large, reaching 64.25%. Dysmenorrhea in adolescent girls that is not managed properly, would disrupt during daily activities which will reduce productivity. One non-pharmacological pain management that can be done during dysmenorrhea is massage. Previous research has proven that massage using a mixture of essential oils in the abdomen and waist area can reduce stomach cramps. The aim of this study was to analyze the effectiveness of lemongrass essential oil massage on reducing dysmenorrhea in adolescent girls at Metland Vocational School. Quasi experimental non control group research design with a one group pretest posttest design approach. The research location is at Metland Vocational School. The sample consisted of 30 girls. The sampling technique used was purposive sampling. The research instrument used a questionnaire. The results of the univariate analysis showed that lemongrass essential oil massage in adolescent girls was able to reduce dysmenorrhea on a pain scale of 5-6 with the criteria of interfering with activities for 15 respondents (50%) to a pain scale of 0 with criteria of no pain for 27 respondents (90%). Bivariate analysis before the data was processed carried out a data normality test, the Shapiro-Wilk test with the result that the data was not normally distributed. The results of the Wilcoxon rank test of lemongrass essential oil massage were able to reduce the dysmenorrhea pain scale in adolescent girls at Metland Vocational School with P= 0.001 (p<0.05). By massaging using lemongrass essential oil, it is effective in reducing dysmenorrhea in adolescent girls so that activities during menstruation are more productive and comfortable.